I need to prove that the series $ \sum \limits_{n=1}^{\infty}\left( \sqrt{1+n^{4}}-n^{2}\right) $ is convergent. But I have kown idea how to prove it. Please anyone give me a help. Thanks.

  • 1
    $\begingroup$ Just to get your thoughts out, may I ask why you think it is convergent? $\endgroup$ – Sujaan Kunalan Mar 11 '15 at 15:54
  • $\begingroup$ If you have no idea how to prove it, why do you think it's convergent...? $\endgroup$ – Hans Lundmark Mar 11 '15 at 16:20

Just write

$$0\le\sqrt{1+n^{4}}-n^{2}=\frac{1}{\sqrt{1+n^{4}}+n^{2}}\le \frac1{2n^2}$$ and use the comparison with the convergent Riemann series $\sum\frac1{n^2}$.


Hint: Observe that for each $n\in \mathbb{N}$,

$$ \left| \sqrt{1+n^{4}}-n^{2}\right|=\sqrt{1+n^{4}}-n^{2}=\dfrac{(\sqrt{1+n^{4}}-n^{2})(\sqrt{1+n^{4}}+n^{2})}{\sqrt{1+n^{4}}+n^{2}}=\dfrac{1}{\sqrt{1+n^{4}}+n^{2}}<\dfrac{1}{n^{2}} $$


$$\sum\limits_{n=1}^{\infty}\dfrac{1}{n^{2}} \text{ is convergent.}$$


Let $$ S = \sum_{n=1}^\infty \left( \sqrt{1+n^4}-n^2\right) = \sum_{n=1}^\infty s_n$$ For all $n>0$, $$1+n^4 > n^4 = (n^2)^2 \Rightarrow \sqrt{1+n^4}-n^2 >0$$ so $S$ is the sum of positive terms, thus to show $S$ is convergent we must merely demonstrate a positive upper bound on $S$. We will do this by demonstrating that the $s_m$ are all less than $t_n$ for a series $T$ which we know to converge:

$$ \sqrt{1+n^4} = n^2 \sqrt{1+\frac{1}{n^4} }< n^2 \left( 1 + \frac{1}{2n} \right) = n^2 + \frac{1}{2n}$$ $$ s_n < \frac{1}{2n^2}$$ and we know that the sum of $\frac{1}{n^2}$ is finite.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.